The Fifth Horseman is Fear - Brynych, Zbynek; Kalis, Jan; Machácek, Miroslav; Scheinpflugová, Olga; Adamíra, Jirí (Facets Video, 2006)
Made during the onset of the Czech New Wave, this powerful tale of personal responsibility is informed as much by Cold War paranoia - and Czech resistance to Soviet impositions - as it is by the torments of the Nazi era. Unquestionably of the '60s in design and scoring, and set chiefly in a single apartment block, the film details the attempts of a Jewish doctor to obtain morphine for an injured resistance figure under police investigation. His internal discussions about when and how one is compelled to help, given his own imminent difficulties, are profoundly moving. Stylised and in places absurdist, with visits to an asylum and a decadent party, it's a striking portayal of a society in moral meltdown, where 'hate's terribly contagious'. The doctor's final act is an absolute attempt to draw a line in the sand against this, and a final measure of commitment to the greater good. [www.timeout.com]